Comparison of in situ ruminal straw fiber degradation and bacterial community between buffalo and Holstein fed with high-roughage diet - Pu, Xuan Xuan; Zhang, Xiu Min; Li, Qiu Shuang; Wang, Rong; Zhang, Min; Zhang, Shi Zhe; Lin, Bo; Tan, Bie; Tan, Zhi Liang; Wang, Min (Frontiers in Microbiology, 2023)
Buffalo exhibits great efficiency in utilizing low-quality roughage, which can be due to the combined effect of host physiological feature and roughage-diet fed. The present study was designed to compare the ruminal fiber degradation and bacterial community attached to straws in Buffalo and Holstein when fed with the same high-roughage diet using in situ ruminal incubation technique. Rice and wheat straws were selected as the incubation substrates, and sampled at 0, 4, 12, 24, 48, 72, 120 and 216 h of incubation time to measure the kinetics of dry matter (DM) and neutral detergent fiber (NDF) disappearance. Additional 2 bags were incubated and sampled at 4 and 48 h of incubation time to evaluate the bacterial community attached to straws. Results showed that Buffalo exhibited greater (P ≤ 0.05) fraction of rapidly soluble and washout nutrient and effective ruminal disappearance for both DM and NDF of straw than Holstein, together with greater (P ≤ 0.05) disappearance rate of potentially degradable nutrient fraction for NDF. Principal coordinate analysis indicated that both host and incubation time altered the bacterial communities attached to straws. Buffalo exhibited greater (P ≤ 0.05) 16S rRNA gene copies of bacteria, and greater (P ≤ 0.05) relative abundance of Ruminococcus attached to straw than Holstein. Prolonging incubation time increased (P ≤ 0.05) the 16S rRNA gene copies of bacteria, and the relative abundance of phyla Proteobacteria and Fibrobacters by comparing 4 h versus 48 h of incubation time. In summary, Buffalo exhibits greater ruminal fiber degradation than Holstein through increasing bacterial population and enriching Ruminococcus, while prolonging of incubation time facilitates fiber degradation through enriching phyla Proteobacteria and Fibrobacteres.